2011
DOI: 10.4161/cbt.12.8.17169
|View full text |Cite
|
Sign up to set email alerts
|

DNA mismatch repair proficiency executing 5-fluorouracil cytotoxicity in colorectal cancer cells

Abstract: IntroductionThe fluoropyrimidine 5-fluorouracil (5-FU) is the cornerstone of chemotherapy and the standard of care for patients with advance staged colorectal cancer (CRC). In particular, 5-FU-based chemotherapy improves survival in patients with stage III colon cancer, 1-3 and in patients with stage II and III rectal cancer. 4 However, individual patient tumor response rates are still overall poor (20-30%), 5 and there is not an efficient method to determine which patient will have the best tumor response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 33 publications
2
31
0
1
Order By: Relevance
“…In experimental studies, hMutSα and hMutSβ participate in recognition of 5FU incorporated within DNA [23,24], which parallels MMR-directed 5FU cytotoxicity, with hMutSα > hMutSβ [25]. Although it has been demonstrated that some components of the tumor microenvironment such as hypoxia diminish DNA MMR repair activity [39–42], there is no data regarding DNA MMR binding or function for 5FU induced cytotoxicity in the typically acidic tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In experimental studies, hMutSα and hMutSβ participate in recognition of 5FU incorporated within DNA [23,24], which parallels MMR-directed 5FU cytotoxicity, with hMutSα > hMutSβ [25]. Although it has been demonstrated that some components of the tumor microenvironment such as hypoxia diminish DNA MMR repair activity [39–42], there is no data regarding DNA MMR binding or function for 5FU induced cytotoxicity in the typically acidic tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…5FU is incorporated into DNA because it is available as a substrate after 5FU's action upon thymidylate synthetase (TS), causing depletion of 2′-deoxythymidine 5′-triphosphate (dTTP). Our demonstration that DNA-containing 5FU specifically triggers a DNA MMR-dependent cell death independent of its RNA actions suggests the importance of 5FU incorporated into DNA for its cytotoxicity [25]. …”
Section: Introductionmentioning
confidence: 99%
“…Hypothetically, 5-FU may cause DNA deterioration, thus accelerating the rates of apoptosis in cancer cells (9,10). However, the effective rate of inducing cancer cell apoptosis for 5-FU was only ~30% with respect to colon cancer clinical chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…We later showed that this had an effect on patient survival from colorectal cancer, as patients with a defective DNA mismatch repair system did not show a survival benefit with adjuvant 5-FU treatment [10]. We worked out the mechanism, showing that individual complexes from DNA mismatch repair had specific binding affinities for 5-FU incorporated into DNA [11, 12] and that isolating the DNA component of 5-FU (from the RNA component) proved that DNA mismatch repair could trigger cell death once it recognizes 5-FU [13]. Talented postdocs Akihiro Tajima, Moriya Iwaizumi, and Yasushi Hamaya [14] were key in figuring out this important process.…”
Section: University Of California San Diegomentioning
confidence: 99%